TERATOMA OF THE KIDNEY: A RARE CASE OF EXTRAGONADAL GERM CELL TUMOR - Tamara R. Panferova; Timur T. Valiev; Oleg P. Bliznyukov; Olga A. Kapkova (Union of pediatricians of Russia, 2017)
For the first time, a clinical observation of a rare case of a mature teratoma of the kidney in a child aged 5 months is presented in domestic literature. A literature review is given on this topic. The clinical picture, characteristic signs of a tumor during ultrasound and X-ray computed tomography, the results of a surgical procedure receive full coverage. Special attention is paid to the morphological characteristics of a mature teratoma.